2010
DOI: 10.3171/2010.1.jns091106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of percutaneous balloon compression and glycerol rhizotomy for the treatment of trigeminal neuralgia

Abstract: Both PRGR and PBC are effective techniques for the treatment of trigeminal neuralgia, with PRGR presenting some advantages in terms of milder and fewer complications and allowing lighter anesthesia without compromise of analgesia. For these reasons the authors consider PRGR as the first option for the treatment of trigeminal neuralgia in patients who are not suitable candidates or are not willing to undergo microvascular decompression, while PBC is reserved for patients in whom the effect of PRGR has proven to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 25 publications
2
38
0
Order By: Relevance
“…In our view, therefore, we would recommend balloon compression as the first-line option. Following our glycerol injections, 72% had complete initial pain relief (with or without medication), comparable with the reported rates of 73-98% in previous studies in the literature [12,13,14,15,16]. Other studies on thermocoagulation report initial complete relief rates between 80 and 100% [17,18,19,20,21], consistent with the 80% value seen here when excellent and good initial relief rates are combined.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In our view, therefore, we would recommend balloon compression as the first-line option. Following our glycerol injections, 72% had complete initial pain relief (with or without medication), comparable with the reported rates of 73-98% in previous studies in the literature [12,13,14,15,16]. Other studies on thermocoagulation report initial complete relief rates between 80 and 100% [17,18,19,20,21], consistent with the 80% value seen here when excellent and good initial relief rates are combined.…”
Section: Discussionsupporting
confidence: 79%
“…This shape corresponds to the anatomy of the interior of Meckel's cave, the dural protrusion around the trigeminal ganglion and the distal trigeminal root [23]. Moreover, we used three cycles of 60-second balloon compression, which may give greater lesions compared with a single cycle reported in some series [12,23], although a study found that the balloon shape (achieving a pear shape, as we aimed for) is more important than the compression time for outcomes [20]. Although the numbness rates we report here are high for balloon compression, we found that the degree of numbness tends to improve with time after the procedure in the majority of cases, and that most patients report that they would accept a degree of numbness if they obtain adequate pain relief from the neuralgia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50,52,[74][75][76][77][78] Fraioli and colleagues, 36 in comparing outcomes for PBC, RFT, and GR, recommended PBC as the first-line choice for percutaneous rhizotomy given its high efficacy rate and low complication rates. Kouzounias and colleagues 75 examined outcomes after PBC and GR, finding comparable rates of initial pain relief for each procedure as well as comparable times to recurrence.…”
Section: Comparative Treatment Efficacymentioning
confidence: 97%
“…They concluded that GR should be the first-line treatment; however, more patients undergoing PBC had previously experienced surgical intervention compared with those who underwent GR, which may explain the higher complication rate seen with PBC. 75 Asplund and colleagues 50 also compared PBC with GR, ultimately recommending PBC as first-line given its lower complication rates. Udupi and colleagues 76 compared outcomes in 40 patients who underwent GR and 39 patients who underwent RFT and found 58.9% of GR patients experienced initial pain relief, compared with 84.6% RFT patients, but this difference was not statistically significant.…”
Section: Comparative Treatment Efficacymentioning
confidence: 98%